STEROID-RESPONSIVE ENCEPHALOPATHY ASSOCIATED WITH AUTOIMMUNE THYROIDITIS: THE OUTCOME OF NEUROLOGICAL AND THYROID STATUS - Tan, Jen Ern; Wong, Sau Wei; Hong, Joyce Soo Synn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Steroid-Responsive Encephalopathy Associated with Autoimmune Thyroiditis (SREAT), also termed as Hashimoto’s Encephalopathy is a neuroendocrine disorder characterized by a triad of subacute onset of encephalopathy, elevated anti-thyroid antibodies, and neurological improvement following steroid therapy. It is a rare but more likely under-diagnosed condition in patients presenting with encephalopathy. CASE A 7-year-old Chinese female was referred for headache, seizures, and mood changes for 2 months. She was found to have hyperthyroidism when she presented with frequent hunger and weight loss 4 months ago. She was started on carbimazole 2.5 mg twice a day and she became euthyroid clinically and biochemically. She was otherwise a brilliant child with no other medical illness. She had no family history of thyroid or autoimmune disorders. Examination revealed an irritable child with upper motor neuron signs. Her cerebrospinal fluid analysis for viral PCR and neuronal antibodies were negative. Her cranial MRI and EEG were reported as normal. Her thyroid function was normal (TSH 3.65 uIU/mL, T4 8.5 pmol/L). Her thyroid antibody levels were all significantly elevated (thyroid stimulating immunoglobulins 3.1 IU/L, anti-thyroid peroxidase antibodies 731.8 IU/ml, anti-thyroglobulin antibodies 642.9 IU/ml). A diagnosis of SREAT was made. She received intravenous methylprednisolone 30 mg/kg/day for 5 days followed by a course of prednisolone for a month. She made a complete recovery. She remained clinically and biochemically euthyroid without medication. A year later, her symptoms recurred, and she was treated similarly as her previous presentation. She recovered but had persistent seizures and needed anti-seizure medication. Her seizure frequency was once a month until 4 years later wherein her seizure frequency increased to weekly without other symptoms. She was given a course of oral prednisolone for 3 months. She was seizure-free for 2 months before her seizures resumed monthly. She was also found to have hypothyroidism (TSH 28.69 uIU/ml, T4 6.65 pmol/L) on screening. She was started on L-thyroxine and became euthyroid after 2 months of treatment. CONCLUSION This case report illustrates that epilepsy is a clinical sequela of SREAT despite being a steroid-responsive condition. Thyroid status does not determine seizure control; hence it reflects an association rather than causation of the encephalopathy.